A current approach to the control of filamentous fungal growth in media: microparticle enhanced cultivation technique. (17th February 2019) - Karahalil, Ercan; Coban, Hasan Bugra; Turhan, Irfan
Abstract: Various strategies have been carried out to date in order to overcome the problem of the adverse effects of bulk fungal growth in bioreactors. Nevertheless, previous conventional methods such as modifying the cultivation temperature or pH resulted in limited biomass production and consequently lower yields. In recent years microparticle enhanced cultivation (MPEC) techniques are one of the most remarkable and novel methods employed for submerged fungal production to overcome bulk microbial growth. In addition to low cost advantages, MPEC also provides benefits such as not interfering with fungal metabolism, enhancing final product concentration and improving homogeneity in the fermentation broth. In this review, a comparison of conventional and novel methods to control fungal morphology has been discussed. Additionally, the application of microparticles in fungal fermentations, their benefits to the process in terms of fungal morphology, biomass accumulation, substrate consumption, and product formation also effect mechanisms of microparticle function are discussed in detail.